ASSESSMENT OF BIOLOGICAL WATER QUALITY OF RIVER GANGA IN PATNA (INDIA) USING BENTHIC MACRO-INVERTEBRATES (Applied Biological Research, 2023)
The present study was carried out to assess the macro-invertebrate diversity  in Patna stretch of river Ganga at four sites during 2017-18. Considering  fluctuations in river hydrology after rainy season, the study was conducted twici.ein summer and late winter. A total 1523 organisms belonging to 11  orders and 43 families were recorded. The operculate members of  Gastropoda were found dominating in summer season at all the sampling  sites and almost identical values of Shannon-Wiener index in river indicated  stabilized ecosystem with moderate level of decomposable organic matter.  Occurrence of pollution-sensitive Ephemeroptera families and good quantityodissolved oxygen at two upstream sites i.e. Digha Ghat and Gandhi Ghat  in winter indicated comparatively good biological water quality of river in  this stretch. Presence of families like Corixidae and Nephthyidae indicated  moderate level of organic matter decay at Malsalami and abundance of  Chironomidae larvae at Fatuha reflected the impact of wastewater discharge  into the river. Gradual decrease in Shannon-Wiener diversity index  supported the impact opollution at these two downstream sites of Patna  stretch of river Ganga.
Keywords: Bio-monitoring; diversity; macro-invertebrates; easonal variation; water quality